New sources of employment to promote the wealth-generating capacity of rural communities - Pakurár, Miklós; Oláh, Judit; Nábrádi, András (Applied Studies in Agribusiness and Commerce, 2012)
New Sources of Employment to Promote the Wealth-Generating Capacity of Rural Communities (acronym: RuralJobs) is a collaborative research project partly funded under the European Commission Research and Development 7th Framework Program. The Rural Jobs consortium consists of partners drawn from eight European Union (EU) countries (Bulgaria, France, Hungary, Italy, Lithuania, Romania, Spain and UK). The project began on February 2008 and finished in October 2010. RuralJobs quantified labour market, demographic and economic trends, and the impact of employment creation measures and policies in seven, representative “reference areas” across the EU, and used the information to demonstrate how rural development measures can be better targeted and how rural development policies should evolve.We identified labour market, demographic and economic trends in rural areas across EU-27 and the potential for new sources of employment outside traditional primary and secondary sector activities, and examined the interaction between different types of rural area (peri-urban, remote, high environmental/amenity value etc.). We identified employment growth areas where rural development programmes can be targeted to increase their contribution to employment creation. Our strategic objectives were the following: review of employment policies and programmes, scenarios for new sources of employment according to rural typologies, recommendations for better targeting of strategies, dissemination and mainstreaming. The main outcome expected is that the results will allow a better targeting of rural development measures and future evolution of rural development policies in line with the Lisbon Strategy.